Evaluation of the usefulness of laparoscopy in the diagnosis and treatment of adnexal pathologies in the pediatric population - Raźnikiewicz, Aleksandra (Wideochir Inne Tech Maloinwazyjne, 2020)
INTRODUCTION: The current trend in adnexal surgery in children is to minimize the invasiveness of diagnostic and therapeutic procedures, reduce the number of complications and reduce the risk of infertility. AIM: Evaluation of the usefulness and effectiveness of laparoscopy in diagnostics and treatment of pathological lesions of adnexa in the pediatric population and evaluation of the correlation of imaging with the intraoperative diagnosis during laparoscopy. MATERIAL AND METHODS: The study included 89 patients aged 0–18 years (mean: 12.62) who underwent an emergency or elective laparoscopic procedure due to the suspicion of adnexa pathology in the imaging tests or in which intraoperative pathology of the adnexa was found without previous suspicion of these changes in the imaging tests. Patients were divided into 2 groups according to the procedure (emergency or elective) and into 4 age groups. RESULTS: The most frequent postoperative diagnosis was an adnexal cyst and ovarian tumor. The ratio of malignant to benign lesions was 0.087. In 32.58% of patients appendix pathology was found. Coexistence of adnexa and appendix pathology was statistically significantly more frequent in patients undergoing emergency surgery (p = 0.013). There was no correlation between the size of the tumor or ovarian cyst and the occurrence of adnexal torsion, and no correlation between the size of the tumor and the degree of torsion of the adnexa. Three conversions were performed. The average operation time was 63.7 min. CONCLUSIONS: Laparoscopic diagnosis and treatment of adnexal pathology seems to be safe due to the low percentage of perioperative complications. It shows high sensitivity in recognizing adnexal pathologies and other defects.